THE EFFECT OF OUTDOOR LEARNING ON TEACHING WRITING OF DESCRIPTIVE TEXT OF TENTH YEAR GRADE STUDENTS’ OF SMA SWASTA TAMANSISWA BINJAI AT ACADEMIC YEAR 2017/2018 - Conny Conny; Shelly Miranti (STKIP Budidaya Binjai, 2018)
This study aimed to find out whether using Outdoor Learning significantly affects on teaching writing of descriptive text of tenth year grade students’ of SMA SWASTA TAMANSISWA Binjai at Academic Year 2017/2018 . In this study, Outdoor Learning as the independent variable (X) and students’ descriptive text as the dependent variable (Y), with the hypothesis: using Outdoor Learning significantly affects on teaching writing of descriptive text of tenth year grade students’ of SMA SWASTA TAMANSISWA Binjai at Academic Year 2017/2018. The population of this study was the tenth year grade students’ of SMA SWASTA TAMANSISWA Binjai, which consisted of 161 sudents. The sample was taken by using random sampling, the total sample was 60 students. Then, the sample was divided into two groups, the group taught by using outdoor learning was as the experimental group and the group taught without outdoor learning was as the control group. The writer used test as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (to) was higher than the value of t-table, (tobserved = 4,13 > ttable = 1,67). Therefore, the hypothesis proposed by the writer was accepted. In the other words, using Outdoor Learning significantly affects on teaching writing of descriptive text of tenth year grade students’ of SMA SWASTA TAMANSISWA Binjai at academic year 2017/2018.Keywords : Outdoor Learning, Teaching Writing, Descriptive Text.